Gamified Listening Activities Powered by Artificial Intelligence: Impact on Secondary Student Engagement and Performance - Yuswandari, Kurnia Devi; Novitaningrum, Angella (Program Studi Pendidikan Bahasa Inggris,, Fakultas Ilmu Pendidikan, Universitas Hasyim Asy'ari, 2025)
This study explored the impact of gamified listening activities powered by artificial intelligence (AI) on secondary students’ engagement and performance in English as a Foreign Language (EFL) learning. Although previous research had highlighted the benefits of both gamification and AI in language education, few studies had examined their combined effects, particularly in listening comprehension at the secondary level. This qualitative research addressed that gap by investigating students’ experiences, engagement levels, and perceived improvements after participating in AI-assisted gamified listening lessons. Using a qualitative case study approach, the research involved three secondary school students who engaged in listening activities through AI-powered gamified platforms such as Quizizz AI, Duolingo, and ChatGPT audio features. Data were collected through classroom observations, reflective journals, and semi-structured interviews to gain in-depth insights into students’ motivation and learning experiences. Thematic analysis was employed to identify key patterns in engagement, emotional response, and perceived performance gains. The findings revealed enhanced motivation, active participation, and improved listening confidence among learners.The significance of this study lies in its contribution as an exploratory examination of how secondary students perceive AI-supported gamified listening activities in an EFL context. Rather than asserting generalizable or significant effects, the findings represent the subjective experiences of the three participants, who reported that the activities felt more engaging, interactive, and personally relevant. These insights are inherently context-specific and should be interpreted with caution, as the limited number of participants restricts the transfer ability of the results. Nevertheless, the study offers preliminary considerations for educators who wish to explore the potential of integrating AI tools and gamification elements into EFL listening instruction, particularly as a means of enhancing learner engagement and personalization.